The Revenant Games - Fuston, Margie (Simon & Schuster, Limited, 2024)
In order to resurrect her sister, seventeen-year-old Bly must win a competition held by warring vampire and witch kingdoms, but things get complicated when she starts to fall for the vampire she is supposed to hand over
Description based on publisher supplied metadata and other sources
Keywords: Vampires; Witches; Contests; Sisters; Paranormal fiction; Romance fiction; Novels